Comparative Relativistic Study of Change in Frequency of Hawking Radiation between XRBS and AGN (Bulletin of Pure and Applied Sciences – Physics, 2022)
The present paper gives the comparative study of change in relativistic frequency of  Hawking radiation due to XRBs and AGN categories of black holes and concludes  that the relativistic change in frequency of Hawking radiation due to XRBs is greater  than to that of AGN category of spinning black holes.